Proteomics shows the role of paederia scandens in ameliorating non-alcoholic fatty liver disease in a rat model - Wang, Jing; Tong, Tiejin; Wu, Qiang (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study was conducted to evaluate the effect of Paederia scandens on high-fat dietinduced non-alcoholic fatty liver disease (NAFLD) in a rat model and further show the therapeutic mechanisms of Paederia scandens. Thirty rats weighing 180 ± 12 g (6 weeks old) were randomly divided into three groups: A control group (CG), a high-fat diet model group (HF), and a Paederia scandens intervention group (PS). After 45 days, the rats’ serum lipid metabolism, liver injury parameters, and liver proteomics were detected. The results indicated that dietary Paederia scandens significantly reduced the levels of triglycerides, total cholesterol, glucose, and low-density lipoprotein cholesterol in the NAFLD rats compared with those in the HF group. Meanwhile, decreased levels of alanine aminotransferase and aspartate transaminase were observed in rats of the PS group. In addition, 382 differentially abundant proteins were identified between the HF and PS groups. Protein-protein interaction network analysis identified 14 keystone proteins that might play critical roles in ameliorating NAFLD. In particular, Paederia scandens treatment significantly upregulated the levels of Hadh, Hadhb, Acadl, Acox1, Acox3, Cyp3a2, and Cyp1a1, which are involved in fatty acid βoxidation, PPAR, and cytochrome P450 signaling pathways. Hence, the data demonstrated that Paederia scandens ameliorates hepatic lipid accumulation and impairment by enhancing fatty acid β-oxidation and activating PPAR and cytochrome P450 signaling pathways. These data provide new insights into the treatment of NAFLD and suggest the potential of Paederia scandens as an effective therapy.